2009
DOI: 10.33151/ajp.7.4.189
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Education of Pre-Employment Paramedic Students during the Clinical Practicum

Abstract: Introduction To identify factors that affect the education of pre-employment paramedic students during the clinical practicum. Methods A purposive sampling technique was employed to recruit undergraduate students from the Bachelor of Emergency Health (Paramedic) (BEHP) who had recently completed their first or final clinical placement. Qualitative data was collected via a total of 3 focus group discussions; two focus group discussions were conducted with students on completion of their final placement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 4 publications
(3 reference statements)
1
20
0
Order By: Relevance
“…Students and preceptors also describe a mismatch of expectations around the ambulance clinical placement (12)(13)(14)(15)(16)(17), leading to misunderstandings on both sides. Other barriers to a positive learning environment include frustration when paramedic preceptors are not aware of students' arrival or their learning requirements, lack of communication between the university and ambulance service, poor mentorship and education by paramedic preceptors, and inadequate support after critical events (15).…”
Section: Ambulance Clinical Placementmentioning
confidence: 99%
“…Students and preceptors also describe a mismatch of expectations around the ambulance clinical placement (12)(13)(14)(15)(16)(17), leading to misunderstandings on both sides. Other barriers to a positive learning environment include frustration when paramedic preceptors are not aware of students' arrival or their learning requirements, lack of communication between the university and ambulance service, poor mentorship and education by paramedic preceptors, and inadequate support after critical events (15).…”
Section: Ambulance Clinical Placementmentioning
confidence: 99%
“…This is a valid educational resource in the same sense as clinical simulations previously demonstrated as effective in paramedic education (15). Fluency in the language of the workplace can assist students to build rapport with clinical staff and this influences student learning in a positive way (7). This serves to improve student knowledge of expectations of them on clinical placements and grows confidence.…”
Section: Discussionmentioning
confidence: 90%
“…Students report unproductive downtime, not being given the opportunity to participate in patient care, and a sometimes-unsupportive learning environment (6). To exacerbate this, the nature of the paramedic workplace means that placements vary significantly in their nature (6) and are therefore of inconsistent quality and value for students, resulting in highly variable learning experiences (7). University educators are therefore faced with the challenge of equipping students to maximise their learning in unreliable and dynamic environments.…”
Section: Introductionmentioning
confidence: 99%
“…However, paramedics suggested that typically graduates lacked essential communication and interpersonal skills, on-road experience and (often) the maturity required to effectively navigate shift work and the professional role of a paramedic (5). Subsequent studies have highlighted the expectations, experiences and foundations of quality clinical placements for undergraduate paramedic students to prepare them for work readiness (4,(6)(7)(8)(9)(10) with recent literature advocating that interprofessional placements in diverse clinical settings are the key to improving undergraduate allied health student knowledge and both clinical and soft skills (2,6).…”
Section: Introductionmentioning
confidence: 99%